Laisser travailler la nature à notre place - Jean Autard (Revue d'anthropologie des connaissances)
In recent years, the ideas of permaculture have been circulating widely in the alternative farming community in France. The emphasis on the self-regulation of cultivated systems and on the reduction of costly and disruptive human interventions leads to the idea of nature's work as a substitute for it. An ethnographic survey of people who practice formal or informal ecologically oriented agriculture reveals the contrasting reception of this idea and the debates it provokes. In doing so, the constitution of practical knowledge with a strong normative dimension is accompanied by a recomposition of the relationship to work and, in particular, the dissolution of the human specificity of work within a holistic frame of reference.